Can HIV recent infection surveillance help us better understand where primary prevention efforts should be targeted? Results of three pilots integrating a recent infection testing algorithm into routine programme activities in Kenya and Zimbabwe. (30th June 2020) - Rice, Brian D; de Wit, Mariken; Welty, Susie; Risher, Kathryn; Cowan, Frances M; Murphy, Gary; Chabata, Sungai T; Waruiru, Wanjiru; Magutshwa, Sitholubuhle; Motoku, John; Kwaro, Daniel; Ochieng, Benard; et al.
Abstract: Introduction: Surveillance of recent HIV infections in national testing services has the potential to inform primary prevention programming activities. Focusing on procedures required to accurately determine recent infection, and the potential for recent infection surveillance to inform prevention efforts, we present the results of three independent but linked pilots of recency testing. Methods: To distinguish recently acquired HIV infection from long‐standing infection, in 2018 we applied a Recent Infection Testing Algorithm that combined a laboratory‐based Limiting Antigen Avidity Enzyme Immunoassay with clinical information (viral‐load; history of prior HIV diagnosis; antiretroviral therapy‐exposure). We explored potential misclassification of test results and analysed the characteristics of participants with recent infection. We applied the algorithm in antenatal clinics providing prevention of mother‐to‐child transmission services in Siaya County, Kenya, outreach sites serving female sex workers in Zimbabwe, and routine HIV testing and counselling facilities in Nairobi, Kenya. In Nairobi, we also conducted recency testing among partners of HIV‐positive participants. Results: In Siaya County, 2.3% (10/426) of HIV‐positive pregnant women were classified as recent. A risk factor analysis comparing women testing recent with those testing HIV‐negative found women in their first trimester were significantly more likely to test recent than those in their second or third trimester. In Zimbabwe, 10.5% (33/313) of female sex workers testing HIV‐positive through the outreach programme were classified recent. A risk factor analysis of women testing recent versus those testing HIV‐negative, found no strong evidence of an association with recent infection. In Nairobi, among 532 HIV‐positive women and men, 8.6% (46) were classified recent. Among partners of participants, almost a quarter of those who tested HIV‐positive were classified as recent (23.8%; 5/21). In all three settings, the inclusion of clinical information helped improve the positive predictive value of recent infection testing by removing cases that were likely misclassified. Conclusions: We successfully identified recently acquired infections among persons testing HIV‐positive in routine testing settings and highlight the importance of incorporating additional information to accurately classify recent infection. We identified a number of groups with a significantly higher proportion of recent infection, suggesting recent infection surveillance, when rolled‐out nationally, may help in further targeting primary prevention efforts.